Identification of metabolic fingerprints in severe obstructive sleep apnea using gas chromatography–Mass spectrometry - Mohit,; Tomar, Manendra Singh; Araniti, Fabrizio; Pateriya, Ankit; Singh Kushwaha, Ram Awadh; Singh, Bhanu Pratap; Jurel, Sunit Kumar; Singh, Raghuwar Dayal; Shrivastava, Ashutosh; Chand, Pooran (Frontiers in Molecular Biosciences, 2022)
Objective: Obstructive sleep apnea (OSA) is considered a major sleep related breathing problem with an increasing prevalence rate. Retrospective studies have revealed the risk of various comorbidities associated with increased severity of OSA. This study was planned to identify novel metabolic biomarkers associated with severe OSA. Methods: Total 50 cases of OSA patients (49.74 ± 11.87 years) and 30 control (39.20 ± 3.29 years) were included in the study. According to the polysomnography reports and questionnaire-based assessment only patients with Apnea Hypopnea index (AHI >30 events/hour) exceeding the threshold representing severe OSA patients were considered for metabolite analysis. Plasma metabolites were analysed using Gas Chromatography-Mass Spectrometry (GC-MS). Results: A total of 92 metabolites were identified in OSA group when compared with Control group after metabolic profiling. Metabolites and their correlated metabolic pathways were significantly altered in OSA patients with respect to controls. The fold change analysis revealed markers of chronic kidney disease, cardiovascular risk and oxidative stress like - indoxyl sulphate, 5-hydroxytryptamine, and 5-aminolevulenic acid, respectively, significantly upregulated in OSA patients. Conclusion: Identifying these metabolic signatures paves the way to monitor comorbid disease progression due to OSA. Results of this study suggest that blood plasma-based biomarkers may have the potential for disease management.